Asset Management Menggunakan QR Code dengan Metode QR Code Generator (Studi Kasus : Badan Narkotika Nasional Karawang) - Satria Adi Nugroho; Arip Solehudin; Didi Juardi (Department of Science and Technology Ibrahimy University, 2021)
The problem that occurs at the Karawang National Narcotics Agency (BNNK) is that there is no information regarding existing asset data, both from the name of the item, year of acquisition, item code, and item serial number. Therefore, the author will create a QR code that contains information about the items in BNNK so that it can be easily accessed and information about these items can be known and can make it easier for employees there when the Ministry of Finance will audit the items related to assets at the BNNK office. Therefore, this study proposes a research related to asset management using a QR code for items at BNNK. The method used in making this QR code is using the QR generator method to simplify the process of making QR codes and making designs for QR codes that will made. For testing the QR code we use beta testing so that we can know in advance the performance and output generated by the QR code. This study produces a QR code that is in accordance with the request of related parties and makes it easier for employees in the goods section to find out data about assets owned by BNNK and help BNNK to carry out asset management on items in the office.